2020
DOI: 10.1016/j.clbc.2019.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 Study of Erlotinib and Metformin in Metastatic Triple-Negative Breast Cancer

Abstract: Purpose: Epidermal growth factor receptor (EGFR) is frequently overexpressed in metastatic triple negative breast cancer (mTNBC). One strategy for overcoming resistance to EGFR inhibition is concomitant inhibition of downstream signaling. The antidiabetic drug metformin inhibits both MAPK and PI3K/mTOR pathway signaling. We evaluated the combination of erlotinib and metformin in a phase 1 study of patients with mTNBC.Patients and Methods: Patients with mTNBC who had received at least one prior line of therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 35 publications
1
16
0
1
Order By: Relevance
“…On the other side, the most common adverse events in both groups were blood disorders, GIT side effects, neuropathic events, fatigue, and hair loss. It is worth mentioning that the metformin group experienced worse GIT symptoms in agreement with the literature 7 , 12 , 16 , 59 , 71 . Besides, it was observed a lower incidence of adverse events; arthralgia, myalgia, and bone pain in the metformin group in comparison to the control arm.…”
Section: Discussionsupporting
confidence: 90%
“…On the other side, the most common adverse events in both groups were blood disorders, GIT side effects, neuropathic events, fatigue, and hair loss. It is worth mentioning that the metformin group experienced worse GIT symptoms in agreement with the literature 7 , 12 , 16 , 59 , 71 . Besides, it was observed a lower incidence of adverse events; arthralgia, myalgia, and bone pain in the metformin group in comparison to the control arm.…”
Section: Discussionsupporting
confidence: 90%
“…A phase 1 study of the erlotinib and metformin combination was conducted in 8 patients with TNBC [ 649 ]. with a fixed dose of erlotinib of 150 mg daily, a 3 + 3 design of metformin dose escalation was evaluated to determine the dose-limiting toxicities (DLTs).…”
Section: Clinical Studiesmentioning
confidence: 99%
“…Findings showing the possible contribution of metformin to reducing the risk of cancer in diabetes patients in 2005 was a prelude to the study of metformin in cancer prevention and treatment [23,27]. A group of clinical trials suggested that metformin showed well-tolerated safe profiles combined with or without traditional or targeted therapies in various cancers [28][29][30][31][32][33][34][35][36]. Clinical applications of metformin in cancer prevention and treatment recently indicated its promising therapeutic effects in colorectal cancer, breast cancer, non-small cell lung cancer, head and neck cancer, and other cancer types, whereas other studies found no beneficial effects in many cancers in non-diabetic patients [37][38][39].…”
Section: Introductionmentioning
confidence: 99%